2014
DOI: 10.1159/000357953
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Ezetimibe by Regulating NF-κB/MAPK Pathway in THP-1 Macrophages

Abstract: Inflammation plays a crucial role in atherosclerosis. Monocytes/macrophages are involved in the inflammatory process during atherogenesis. Here, we performed daily gavage of ezetimibe in apolipoprotein E-deficient mice fed with a high-fat diet and found that ezetimibe administration decreased the level of C-reactive protein significantly. To investigate the potential molecular mechanism, we employed microarray analysis on the cultured macrophages treated with Chol:MßCD in the presence or absence of ezetimibe. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It has been reported that ezetimibe confers additional beneficial effects other than lowering blood lipid levels. In animal models, ezetimibe reduced inflammatory response [50][51][52] and promoted autophagy, which resulted in neuroprotection or improvement of nonalcoholic fatty liver disease (NAFLD) [24,53] via AMP protein kinase (AMPK) activation and inhibition of NLR family pyrin domain containing 3 (NLRP3) inflammasome [23]. In addition, ezetimibe is known to activate nuclear factor erythroid 2-related factor 2 (Nrf2) and to reduce oxidative stress in animal models [54].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ezetimibe confers additional beneficial effects other than lowering blood lipid levels. In animal models, ezetimibe reduced inflammatory response [50][51][52] and promoted autophagy, which resulted in neuroprotection or improvement of nonalcoholic fatty liver disease (NAFLD) [24,53] via AMP protein kinase (AMPK) activation and inhibition of NLR family pyrin domain containing 3 (NLRP3) inflammasome [23]. In addition, ezetimibe is known to activate nuclear factor erythroid 2-related factor 2 (Nrf2) and to reduce oxidative stress in animal models [54].…”
Section: Discussionmentioning
confidence: 99%
“…This anti-inflammatory action of ezetimibe is partially consistent with a previous report showing that ezetimibe inhibited expression of CRP (C-reactive protein), TNF, and NFKB in THP-1 macrophages. 32 Recently, cell-cell interaction through exosomes was elucidated as a crucial factor in the development of NAFLD and NASH. 33 Exosomes, which contain proteins, mRNAs, and miR-NAs, are released by several cell types into biological fluids and taken up by endocytosis into different cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is likely based on both a distinct LDL-cholesterol reduction by combining statins with ezetimibe and an additional independent anti-inflammatory component as well [13,31]. Experimental data advise an ezetimibe-mediated inhibition of transendothelial monocyte migration threw regulation of the NF-κB/MAPK pathway in rabbits and mice as one potential mechanism [32,33]. Yet, additional pleiotropic, anti-inflammatory effects through statin therapy besides cholesterol reduction have already been demonstrated in a large clinical collective [6].…”
Section: Discussionmentioning
confidence: 99%